2021
DOI: 10.1039/d1ob01377g
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free formal [3 + 2] cycloaddition of stabilized N,N-cyclic azomethine imines to 3-nitrobenzofurans and 3-nitro-4H-chromenes: access to heteroannulated pyrazolo[1,2-a]pyrazoles

Abstract: We have studied the [3 + 2]-cycloaddition of various N,N-cyclic azomethine imines to 3-nitrobenzofurans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In a subsequent report, Osipov and co‐workers demonstrated that N,N ‐cyclic azomethine imines 122 were suitable reaction partners in 1,3‐dipolar dearomative cycloaddition with 3‐nitrobenzofurans (Scheme 23B) [34] . This reaction also did not require any catalyst and proceeded at room temperature in DMSO as the solvent, allowing the diastereoselective synthesis of a variety of benzofuro [2,3‐ c ]pyrazolo[1,2‐ a ]pyrazole scaffolds 123 .…”
Section: [3+2] Dearomative Annulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent report, Osipov and co‐workers demonstrated that N,N ‐cyclic azomethine imines 122 were suitable reaction partners in 1,3‐dipolar dearomative cycloaddition with 3‐nitrobenzofurans (Scheme 23B) [34] . This reaction also did not require any catalyst and proceeded at room temperature in DMSO as the solvent, allowing the diastereoselective synthesis of a variety of benzofuro [2,3‐ c ]pyrazolo[1,2‐ a ]pyrazole scaffolds 123 .…”
Section: [3+2] Dearomative Annulationmentioning
confidence: 99%
“…In a subsequent report, Osipov and co-workers demonstrated that N,N-cyclic azomethine imines 122 were suitable reaction partners in 1,3-dipolar dearomative cycloaddition with 3-nitrobenzofurans (Scheme 23B). [34] This reaction also did not require any catalyst and proceeded at room temperature in DMSO as the solvent, allowing the diastereoselective synthesis of a variety of benzofuro [2,3-c]pyrazolo[1,2-a]pyrazole scaffolds 123. However, 3-nitroindole, 3-nitrobenzothiophene and 2nitrobenzofuran were not suitable substrates for this protocol, and cycloaddition to azomethine imines did not occur in DMSO at room temperature and even at 70 °C.…”
Section: Cyclic Azomethine Iminesmentioning
confidence: 99%
“…Thus, we have found that 3nitrobenzofurans react with N,N-cyclic azomethine imines to form the formal [3 + 2]-cycloaddition products. 22 In addition, we have shown that 3-nitrobenzofurans react with 2-(1arylethylidene)malononitriles, 23a carbonyl-stabilized sulfonium ylides, 23b and aromatic amines 23c with the ring-opening of heterocyclic fragment. In continuation of our studies of the dearomatization of 3-nitrobenzofurans, as well as our research interest in chemistry of push−pull heterocycles, 22−24 we focused our attention on the formal [3 + 2]-cycloaddition of 3-nitrobenzofurans with carbonyl-stabilized quinolinium and isoquinolinium ylides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To the best of our knowledge, such a method for the preparation of benzo-and naphthofurans was not described earlier, while ring contraction reactions of 2H-and 4H-chromenes are limited to a few examples and remain underdeveloped. 3 Besides, the naphtho [2,1-b]furan skeleton constitutes a key structural element in many biologically active compounds, primarily anticancer agents (compounds A and B), 4 and is present in a number of natural products of plant origin. Among them there are furanocadalene (C) and laevigatin (D) isolated from Chromolaena laevigata as well as benzofuro [4,5-f ]chromene (E) from Juncus acutus (Figure 1).…”
mentioning
confidence: 99%
“…In recent years, electron-deficient chromenes have attracted increasing interest due to their unique reactivity providing access to various heterocyclic systems. Among them, 3-nitro-2 H -chromenes and closely related but much less studied 3-nitro-4 H -chromenes attract the most attention, since the strong polarization of the double bond in the pyran ring makes them susceptible to an attack by nucleophiles and provides wide possibilities in heterocyclization processes . In the structure of 3-nitro-4 H -chromenes, the presence of of an oxyvinyl moiety conjugated to the electron-withdrawing group permits these compounds to be regarded as push–pull olefins and makes them masked equivalents of highly electrophilic α-nitroaldehydes (Scheme a).…”
mentioning
confidence: 99%